2020
DOI: 10.1037/spy0000162
|View full text |Cite
|
Sign up to set email alerts
|

The quiet eye effect: A test of the visual and postural-kinematic hypotheses.

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 50 publications
0
14
2
5
Order By: Relevance
“…The value of QE is not necessarily a net reduction of fluctuations but rather a way to train athletes to orient their movements towards the optic flow generated by postural sway. Whereas the postural-kinematic hypothesis had previously only referred to longer movement duration [22], we now report that movements are not merely slower but evince a sort of nonlinearity constricting the degrees of freedom across scales of the movement-system hierarchy. In one of the subsections below, we discuss how this orienting towards optic flow might coordinate with mechanisms invoked by the more elaborate visual hypothesis (e.g., [61,62]).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The value of QE is not necessarily a net reduction of fluctuations but rather a way to train athletes to orient their movements towards the optic flow generated by postural sway. Whereas the postural-kinematic hypothesis had previously only referred to longer movement duration [22], we now report that movements are not merely slower but evince a sort of nonlinearity constricting the degrees of freedom across scales of the movement-system hierarchy. In one of the subsections below, we discuss how this orienting towards optic flow might coordinate with mechanisms invoked by the more elaborate visual hypothesis (e.g., [61,62]).…”
Section: Discussioncontrasting
confidence: 55%
“…Research on QE has mostly examined the visual-cognitive bases for the relatively more extraverted gaze into the task context (Panchuk & Vickers, 2006; Rienhoff et al, 2016; Vickers, 2011), and the relationship of QE to the body, the brain, and the nervous system has received relatively less attention (Davids & Araújo, 2016; Renshaw et al, 2019; Shine et al, 2018). To fill this gap, a ‘postural-kinematic hypothesis’ has begun to complement the canonical ‘visual hypothesis’ that QE was a primarily visual-cognitive mechanism (Gallicchio & Ring, 2020). So far, this postural-kinematic hypothesis emphasizes only slower movement times, that is, longer duration offering the foundation for longer fixations.…”
Section: Introductionmentioning
confidence: 99%
“…This might be a technical limitation of QE training. Although a recent study suggested that electrooculogram recording could evaluate QE as a replacement for an eye-tracker system (Mann et al, 2011;Gonzalez et al, 2017a;Gallicchio et al, 2018;Gallicchio and Ring, 2019), this still requires equipment for psychophysiological recordings. Therefore, it could be beneficial if a reliable method that guarantees prolongation of QE without any special equipment is established.…”
Section: Introductionmentioning
confidence: 99%
“…QE fixations within 3 degrees of visual angle of the ball equate to ∼8 cm either side of the ball for an average height adult; a sizable variation in location. The precision of current mobile eye tracking technology has also been a barrier to investigating the relative functional role of the specificity of the location and whether a ‘quieter eye’ that remains within one degree is better than a fixation within three degrees (Gallicchio et al, 2017; Gallicchio & Ring, 2019).…”
Section: Experiments 1: Locationmentioning
confidence: 99%